The amazonic fundaments in the ancient prehispanic religión. The bats in the symbolism of them Chavin - Wong Robles, Antonio Ruben (2009)
This paper shows the relationship between the most important representations of Chavin style and the graphical representation of the bat as a token representative of a social group of wild and selvatic origin eminently